2021
DOI: 10.3390/pr9122175
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection By-Products (DBPs) in Seawaters, Sediments and Biota near a Marine Terminal for Regasifying Liquefied Natural Gas (LNG) in the Northern Adriatic Sea (Italy)

Abstract: In 2009, the first Italian offshore LNG terminal, located approximately 12 km from the coast of Italy in the Northern Adriatic Sea, started its operation phase. Even if the active chlorine concentration in the discharged seawater is within limits set by Italian regulations (0.2 mg/L), to verify the environmental impact of disinfection by-products (DBPs) on the ecosystem, a specific monitoring program was scheduled from 2010 to 2015. The present study is the first displaying results of DBPs in marine waters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Both Gibson et al 83 and Iibuchi et al 80 demonstrated successful THM purging within a short period of hours, that is, much shorter than the purging of off-flavour chemicals (geosmin and MIB), which may take up to 14 days. Available data 60,80,82,83 refer only to THM removal, while further studies must be developed for the removal of haloacetic acids, 85 dichloroacetonitrile 86 and any other bioaccumulated DBPs. Future studies should include DBPs removal for a range of RAS-cultured fish species (with different fat contents) and diverse water characteristics to assure that fish that are grown in a facility that includes a disinfection unit would be supplied with safe levels of accumulated DBPs.…”
Section: Disinfection Byproducts (Dbp)mentioning
confidence: 99%
“…Both Gibson et al 83 and Iibuchi et al 80 demonstrated successful THM purging within a short period of hours, that is, much shorter than the purging of off-flavour chemicals (geosmin and MIB), which may take up to 14 days. Available data 60,80,82,83 refer only to THM removal, while further studies must be developed for the removal of haloacetic acids, 85 dichloroacetonitrile 86 and any other bioaccumulated DBPs. Future studies should include DBPs removal for a range of RAS-cultured fish species (with different fat contents) and diverse water characteristics to assure that fish that are grown in a facility that includes a disinfection unit would be supplied with safe levels of accumulated DBPs.…”
Section: Disinfection Byproducts (Dbp)mentioning
confidence: 99%